The influence of youtube food content reviews on customer purchasing decisions: lesson from Jakarta local street food - wachyuni, suci sandi; Kadek Wiweka; Nenny Wahyuni; Shinta Teviningrum; Heru Suheryadi (International Journal of Applied Sciences in Tourism and Events, 2023)
The purpose of this study is to examine the influence of food review content on YouTube on purchasing decisions for local culinary delights, specifically the Jakarta Nasi Goreng Kambing Kebon Sirih. It is the one of the favorite culinary place in Jakarta which sells lamb fried rice, it is located at Kebon Sirih Street. This research employed a quantitative approach with data analysis techniques such as descriptive statistics, linear regression test, t test, and coefficient of determination. The participants in this study are tourists on culinary trips in Jakarta. The samples were 100 tourists who went on a culinary trip and purchased fried rice for the Jakarta Kebon Sirih utilising non-probability sampling or purposive sampling techniques. The correlation coefficient test findings reveal that food reviews on YouTube have a remarkably strong relationship with Nasi Goreng Kambing Kebon Sirih purchasing decisions. Furthermore, the t test results indicate that food reviews on YouTube have a partially positive influence on the decision to purchase culinary products at the restaurant. The theoretical implication of this research is to provide an understanding that food reviews on YouTube have a significant contribution in the context of culinary products or culinary tourism. In the meantime, the findings of this study can be utilized as a reference for restaurant management in particular, and for local street food in general. Some of the limitations of this research that can be addressed in future research include the sample size and research scope.